Application of network pharmacology in the study of the mechanism of action of traditional chinese medicine in the treatment of COVID-19 - Zheng, Shihao; Xue, Tianyu; Wang, Bin; Guo, Haolin; Liu, Qiquan (Frontiers in Pharmacology, 2022)
Network pharmacology was rapidly developed based on multidisciplinary holistic analysis of biological systems, which has become a popular tool in traditional Chinese medicine (TCM) research in recent years. Its characteristics of integrity and systematization provide a new approach for the study on complex TCM systems, which has many similarities with the holistic concept of TCM. It has been widely used to explain the mechanism of TCM treatment of diseases, drug repositioning, and interpretation of compatibility of TCM prescriptions, to promote the modernization of TCM. The use of TCM have provided crucial support on prevention and treatment of diseases such as the famous "three medicines and three prescriptions". Furthermore, TCM has become an important part of the treatment of COVID-19 and is one of the main contents of the "Chinese plan" to fight the epidemic. The current review demonstrated the role of TCM in treating diseases with multiple components, multiple targets, and multiple pathways, interprets the connotation of TCM treatment method selection based on pathogenesis and also discusses the application of network pharmacology in the study of COVID-19 treatment in TCM including single drug and prescription. However, there are still some shortcomings such as the lack of experimental verification and regular upgrading of the TCM pharmacology network. Therefore, we must pay attention to the characteristics of TCM and develop a network pharmacology method suitable for TCM system research when applying network pharmacology to TCM research.